Prevalence of Deviated Nasal Septum among Nepalese Preclinical Students at Kathmandu Medical College Teaching Hospital, Nepal - Tiwari, Nripendra; Budhathoki, Deepesh; Shrestha, Iju; KC, Gopal (Journal of Universal College of Medical Sciences, 2018)
Introduction: The fragile nature of the nasal septum and other bony structures makes them prone to fragmentation and destruction. Deviated nasal septum persists in adult stage of life giving rise to anatomical, psychological and cosmetic consequences. There are many consequences of deviated nasal septum like nasal obstruction, mouth breathing, headache and asymmetry of face. The amount of airflow and resistance to it in the nasal cavity with deviated nasal septum are quite different from person to person. Our study is focused on the prevalence of deviated nasal septum. Materials and methods: This was a cross-sectional observational study conducted among 300 individuals from Nepalese preclinical students studying at Kathmandu Medical College Teaching Hospital (KMCTH). Prevalence of deviated nasal septum in males and females were determined affecting symmetry of the face. Results: The prevalence of deviated nasal septum was found to be 53% (159) of total study population. The left sided nasal septal deviation was found to be more in male 33.33% (50) than that of female 29.33% (44).The asymmetry of the face was observed in 55% (165) of total study population. However, asymmetry of face was observed more in male 58.66% (88) than in female 51.33% (77). Conclusion The deviated nasal septum and asymmetry of the face were remarkably prevalent among Nepalese preclinical students studying at Kathmandu Medical College Teaching Hospital. The prevalence of deviated nasal septum and asymmetry of face was found significantly greater in male than in female (p< 0.05).